Profile and Description of Injury Victims Died due to Traffic Accidents on Motorcycle Riders at the Forensic Section of Dr. RSUP. M. Djamil Padang Year 2018 – 2019 - Rika Susanti; Anggi Rahmi Rusadi; Fory Fortuna (Journal of Midwifery, 2021)
Backgrounds: Fatalties and injuries in traffic accidents are a serious problem of the world and show that will continue to occur in the future. The cause of injury in traffic accidents mostly occurs in motorcyclists.Objectives: To know the profile and patterns of injury in victims who died due to accidents on motorcyclist at the Forensic Department of RSUP Dr. M. Djamil Padang 2018 – 2019Methods: This is a retrospective descriptive study with a total population sampling design. Data of the victims was taken from secondary data in the Forensic Department of Dr. M. Djamil Hospital, Padang for the period 2018 – 2019.Results: The study showed that a total of 74 victims who died mostly found in men (89.2%) and in the 22-40 year age group (28.4%). Based on the location and types of the injury, the most common injuries were to the head (31%), and abrasions (62%). The location of the victim's death was mostly found in the scope of the hospital with the most length of stay, namely 0 - 3 days and types of acceptance were the reference victims.Conclusion: Victims who died mostly found in males and ages from 22 to 40 years, so it is necessary to conduct socialization on the dangers of death to motorcyclists as well as outreach efforts to the community, especially young people, about traffic awareness and behavior